Legal And Criminal Profiling Issues Of Persons Supporting Armed Aggression In Ukraine - Podzolkova, Tetiana; Shynkarenko, Ihor (Archives of Criminology and Forensic Sciences, 2026)
In current conditions caused by Russia’s military aggression in Ukraine, in which Russian militaries endanger a threat to nuclear facilities in the territory of Ukraine, kills, maims and tortures civilians, the use of innovative profiling technique in combating wartime crime is becoming highly important. Since the invasion of Ukraine, Russian troops have bombarded civilian infrastructure, fired at ambulances, destroyed hospitals, orphanages, residential buildings, kindergartens and schools. Therefore, the Article Purpose is to specify existing issues of applying the profiling method to prevent, detect and eliminate current threats to the state and society that have become relevant not only for Ukraine but also for the majority countries of the world.